Improving rural water supply in Paraguay in times of COVID-19 - Silva, Jorge (Tecnología y ciencias del agua, 2023)
Water supply and access has gained widespread attention especially with the ongoing coronavirus pandemic. Summations from the documents show that the pandemic has led to investors holding out on channeling funds into water systems in Paraguay, thus leaving people in rural areas being unable to gain basic protection against the virus. The challenges faced are explored in the subsequent systematic review. Results show that Paraguay has a more than functional water system, which can, however, be improved through collaboration between private and government entities. Recommendations drawn call on the involvement of all stakeholders in decision making to find an iron-clad solution to the issue.